The Influence of Interfunctional Collaboration on Management Traffic by Operations through AOCC Performance at Ngurah Rai Airport - Binsar Reynold; Juliater Simarmata; Yulianti Keke; Erwansyah Sjarief (Dinasti Publisher, 2026)
I Gusti Ngurah Rai International Airport in Bali is one of the busiest airports in Indonesia, serving over 19 million passengers in 2023. With an average of 390 aircraft movements per day and a high proportion of international wide-body flights, the airport faces increasing operational complexity. Challenges such as limited apron space, slot overlaps, and fragmented coordination among stakeholders often result in delays and reduced passenger satisfaction. This study aims to analyse the influence of interfunctional collaboration on traffic operation management performance through the roles of AOCC service quality and performance. Using a quantitative descriptive approach, the study involves 150 respondents selected through stratified random sampling. Primary data were collected via questionnaires, supported by secondary data such as operational reports and previous research. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4.0. These findings demonstrate that the implementation of A-CDM and a well-performing AOCC plays a crucial role in supporting airport operational resilience. Strengthened coordination, data-driven resource allocation, and integrated monitoring systems under A-CDM collectively contribute to better management operations by Traffic, improving not only operational efficiency but also overall passenger experience at Ngurah Rai Airport.